Noradrenergic dysfunction in Alzheimer's disease - Gannon, Mary; Che, Pulin; Chen, Yunjia; Jiao, Kai; Roberson, Erik D.; Wang, Qin (Frontiers in Neuroscience, 2015)
The brain noradrenergic system supplies the neurotransmitter norepinephrine throughout the brain via widespread efferent projections, and plays a pivotal role in modulating cognitive activities in the cortex. Profound noradrenergic degeneration in Alzheimer’s disease (AD) patients has been observed for decades, with recent research suggesting that the locus coeruleus (where noradrenergic neurons are mainly located) is a predominant site where AD-related pathology begins. Mounting evidence indicate that the loss of noradrenergic innervation greatly exacerbates AD pathogenesis and progression, although the precise roles of noradrenergic components in AD pathogenesis remain unclear. The aim of this review is to summarize current findings on noradrenergic dysfunction in AD, as well as to point out deficiencies in our knowledge where more research is needed.